PENGARUH LABORATORIUM TERHADAP HASIL BELAJAR MELALUI MINAT BELAJAR PADA MATA PELAJARAN KELOMPOK C3 PROGRAM KEAHLIAN PEMASARAN KELAS XI SMK NEGERI 1 KARANGANYAR TAHUN AJARAN 2017/2018â€ - -, Irvan Yanuarta -; -, Mintasih Indriayu -; -, Sudarno - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The purpose about this research is 1) for informing the impact of laboratory to learning outcomes through by the interesting subject on group C3 marketing class grade XI SMK 1 Karanganyar year 2017/2018, 2) for knowing the impact of laboratory to learning outcomes on group C3 marketing class grade XI SMK 1 Karanganyar year 2017/2018, 3) for knowing the interest learning as mediating variable to learning outcomes on group C3 marketing class grade XI SMK 1 Karanganyar year 2017/2018. Sampling technique is Proportional Random Sampling. The sum of sample is 60 respondent. Data collection technique by questionnaire and documentation. The data analysis that writer used is Partial Least Square (PLS).               The result of this research showing that the laboratory through by the interesting subject produce t-statistic in amount of 2,050, so it can be known that value t-statistic greater than alpha (2,050>1,96), while the value of p-value is 0,041 less than 0,05, original sample showing the positive value 0,279. The result show that laboratory through by interesting subject significant so that can take effect to learning outcomes and state that laboratory through by the interesting subject take positive effect to learning outcomes.            Based on the result research can conclude that (1) laboratory take positive effect and significant to learning outcomes through by the interesting subject which can be shown by p-value 0,041<0,05, (2) laboratory take positive effect and significant to learning outcomes which can be shown by p-value 0,010<0,05, (3) the interesting subject as mediating variable take positive effect and significant to learning outcomes which can be shown by p-vlue 0,019<0,05, and R square value 57,5%. So it can be show that laboratory through by the interesting subject can explain the result of learning outcomes 57,5%, while the rest is 42,5% explained by the other research variable.